2011
DOI: 10.1089/fpd.2011.0862
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Investigation of a Diffuse Outbreak Caused bySalmonella entericaSerotype Montevideo Isolates in Osaka Prefecture, Japan

Abstract: In Osaka Prefecture, Japan, three foodborne outbreaks were caused by Salmonella enterica serotype Montevideo in rapid succession between September 2007 and May 2008. Further, Salmonella Montevideo was also isolated from several sporadic diarrhea patients and asymptomatic carriers examined during approximately the identical period. To investigate the relatedness of the isolates, we performed antimicrobial susceptibility testing, pulsed-field gel electrophoresis (PFGE) analysis, and multiple-locus variable-numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…When using two restriction enzymes, XbaI and BlnI, a group in Japan found them useful to discriminate between S. Montevideo isolates. 33 In conclusion, this study revealed that S. Enteritidis and S. Typhimurium remained the two most common Salmonella serovars isolated in Hong Kong. There was a significant increase in resistance to the fluoroquinolones and multidrug resistance but resistance to the third generation cephalosporins remained low.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…When using two restriction enzymes, XbaI and BlnI, a group in Japan found them useful to discriminate between S. Montevideo isolates. 33 In conclusion, this study revealed that S. Enteritidis and S. Typhimurium remained the two most common Salmonella serovars isolated in Hong Kong. There was a significant increase in resistance to the fluoroquinolones and multidrug resistance but resistance to the third generation cephalosporins remained low.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, other typing methods, namely multiple-locus variable-number tandemrepeat analysis (MLVA) and multilocus sequence typing (MLST), have been used to type salmonellae. 33,34 MLST was shown not to be as good as PFGE owing to the lack of diversity of the housekeeping genes. 34 MLVA was also not a desirable method.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic Salmonella infections have been reported in previous studies in several countries including Japan, Hong Kong, and Malaysia (Bakeri et al, 2003;Harada et al, 2011;Liang et al, 2007;Tassios et al, 1997;Thong et al, 1994;Tsen et al, 2001). In a study by Bakeri et al (2003), a single PFGE pattern, PFP X1, predominated in human SE isolates obtained from different parts of Malaysia from 1995 to 2001, and this particular clone was endemic in Malaysia.…”
Section: Discussionmentioning
confidence: 85%
“…Among genotypic methods, pulsed-field gel electrophoresis (PFGE) is used by the PulseNet program, a molecular subtyping network for foodborne bacterial disease surveillance at the United States Centers for Disease Control and Prevention, to identify widespread outbreaks of bacterial foodborne illness (Foley et al, 2006;Swaminathan et al, 2006). In addition to PGFE, multiple-locus variable number tandem repeat analysis (MLVA) is also useful for discriminating among isolates that are indistinguishable by PFGE (Malorny et al, 2008;Harada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PCR reaction mixtures were prepared using puReTaq Ready-To-Go PCR Beads (GE Healthcare, Piscataway, N.J., USA) containing the primers shown in Table 2 and 2 ml of DNA template in a final volume of 25 ml. The amplification conditions used in this study have been described previously (13). The amplified PCR products were electrophoresed in 2.0z (w/v) agarose gels and visualized by staining with ethidium bromide and viewing under UV light.…”
mentioning
confidence: 99%